Ts'ao Yu, The Reluctant Disciple of Chekhov and O'Neil : A Study in Literary Influence - Lau, Joseph S. M., 1934- (Centre of Asian Studies series, 1970)
Historians of modern Chinese literature have generally used the year 1907 to mark the inception of Western-style drama in China. For in that year, a small group of Chinese students in Japan, inspired by the Japanese experiments with Western drama, decided to follow suit and form the Spring Willow Society, an amateurish dramatic club for experimental purposes. Their first play, staged in Tokyo in February of the same year, is an adaptation from Dumas' La dame aux camelias. The play had an all-male cast and used a strange mixture of old and new techniques. But to the Chinese audience brought up in the native operatic tradition, what must have seemed strange would not have been so much the mixture of technique old and new as the complete unfamiliarity of the plot and the method of its presentation: for neither the story nor the acting was anything akin to what they used to think, of as drama.